Identifikasi Tipologi Bangunan Stasiun Kereta Api Temanggung, Jawa Tengah - Abimanyu, Yosa; Zuhri, Syaifuddin (Politeknik Negeri FakFak, 2024)
With the railway line reactivation plan in accordance with the Ministry of Transportation's RIPNAS 2011, a heritage management system is needed because this station is a historic building. Building typology analysis is the first step in implementing this system. This research uses a qualitative descriptive method by making direct observations at the Temanggung Train Station building and also looking for data sources from several existing references. Thus, this research aims to explore the historical value and typology of train stations in Temanggung. So that steps can be taken to determine a heritage management system to prepare a reactivation plan for the route. The results obtained show that the typology of the train station buildings in Temanggung Regency is a transitional colonial architectural style, seen from the building typology.